Millimeter-scale growth of highly ordered CsPbBr3 single-crystalline microplatelets on SiO2/Si substrate by chemical vapor deposition. (8th June 2021) - Song, Jiepeng; Li, Chun; Shang, Qiuyu; Ke, Yuxuan; Zhao, Liyun; Liang, Yin; Zhang, Li; Zhang, Qing
Abstract: Recently, all-inorganic cesium lead bromide (CsPbBr3 ) perovskite has attracted tremendous interest due to its promise for green light photonic and optoelectronic devices. The growth of high-quality planar micro-/nano-structures of CsPbBr3 on the technologically important silicon substrate is an important issue for these applications, which has not yet been well explored. Herein we fabricate millimeter-scale single-crystalline CsPbBr3 microplatelets (MPs) on SiO2 /Si substrate by chemical vapor deposition. A preferred growth direction is demonstrated with the [110] direction parallel to the flux direction of carrier gas. Strong green emission is observed at room temperature with superior photo-stability, long lifetime, and excitonic features. Furthermore, the room temperature whispering-gallery-mode lasing is achieved from the focused ion beam fabricated microdisks with the thresholds comparable to those of pristine square MPs. These results suggest the great potentials of CsPbBr3 MPs for the Si-based photonic devices.